1994
DOI: 10.1073/pnas.91.10.4362
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization of Borna disease virus.

Abstract: Borna disease virus is a neurotropic negativestrand RNA virus that infects a wide range of vertebrate hosts, causing disturbances in movement and behavior. We have cloned and sequenced the 8910-nucleotide viral genome by using RNA from Borna disease virus particles. The viral genome has complementary 3' and 5' termini and contains antisense information for five open reading frames. Homology to Filoviridae, Paramyxoviridae, and Rhabdoviridae is found in both cistronic and extracistronic regions. Northern analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
333
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(341 citation statements)
references
References 28 publications
6
333
1
1
Order By: Relevance
“…Borna disease virus (BDV) is a noncytolytic, neurotropic, single strand, negative sense RNA virus that naturally infects a wide range of vertebrate species from birds and rodents to primates [1,3]. BDV can also cause encephalomyelitis in a wide range of experimental animals [5,6,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Borna disease virus (BDV) is a noncytolytic, neurotropic, single strand, negative sense RNA virus that naturally infects a wide range of vertebrate species from birds and rodents to primates [1,3]. BDV can also cause encephalomyelitis in a wide range of experimental animals [5,6,14].…”
mentioning
confidence: 99%
“…Borna disease virus (BDV) is a noncytolytic, neurotropic, single strand, negative sense RNA virus that naturally infects a wide range of vertebrate species from birds and rodents to primates [1,3]. BDV can also cause encephalomyelitis in a wide range of experimental animals [5,6,14].In domestic cats, an characteristic disease of the central nervous system has been observed in Sweden [9]; the dominating clinical sign is an unsteady (staggering) gait. Histopathological examination of the cats showed that the inflammatory reaction of the central nervous system was most pronounced in the grey matter of the brain stem, basal ganglia and hippocampus.…”
mentioning
confidence: 99%
“…Two isolates (reference strains V and He/80) were recently completely sequenced. BDV was classified into the Mononegavirales order and it is the only prototype of the new Bornaviridae family within this order [9,15].…”
Section: Classification Of Bdvmentioning
confidence: 99%
“…virus Borna / PCR / témoin interne / tissu biologique partial segment 2 of serotype 3 sequence and the primer recognition sites of two BDV targets: the p40 genomic region coding the nucleoprotein, and the p24 genomic region coding the phosphoprotein known as a cofactor of the BDV polymerase [4]. Since it contains another genomic fragment between the primer sites, this molecule cannot form a heteroduplex with the test template.…”
Section: Introductionmentioning
confidence: 99%